Reseña CROSSCULT. Empowering Reuse of Digital Cultural Heritage in Context-Aware Crosscuts of European History - Bocanegra Barbecho, Lidia (Revista de Humanidades Digitales, 2019)
LYKOURENTZOU, Ioanna, NAUDET, Yannick, VANDENABEELE, Luc, LÓPEZ NORES, Martín, VASSILAKIS, Costas, BIKAKIS, Antonis, SOLANO, Jaime, GIANNAKOPOULOS, Giorgios, VASILAKAKI, Evgenia, PAZOS ARIAS, José Juan. CROSSCULT. Empowering Reuse of Digital Cultural Heritage in Context-Aware Crosscuts of European History. Coord. Luxembourg Institute of Science and Technology, 2016-2019. https://www.crosscult.eu/ https://cordis.europa.eu/project/rcn/200492/factsheet/en